Maternal size in perch (Perca fluviatilis) influences the capacity of offspring to cope with different temperatures - Hall, Marcus; Nordahl, Oscar; Forsman, Anders; Tibblin, Petter (Frontiers in Marine Science, 2023)
Climate change causes earlier and warmer springs in seasonal environments and a higher incidence of extreme weather events. In aquatic environments, this changes the thermal conditions during spawning, and the thermal performance of eggs and embryos may determine the consequences of climate change on recruitment. In iteroparous species with indeterminate growth, the eggs produced by a given female in successive years will increase in size as the female grows larger and likely be exposed to different temperatures during incubation due to annual variation in spring phenology. Still, we know little about whether differences in maternal size impact the temperature-dependent performance and viability of the offspring. Here we utilised a thermal gradient laboratory experiment on Baltic Sea perch (Perca fluviatilis) to investigate how maternal size influence the temperature dependent hatching success of the offspring. The results uncovered a positive relationship between maternal size and average hatching success, but the shape of the relationship (reaction norm) linking hatching success to incubation temperature was independent of maternal size. However, we did find an association between maternal size and the variance (S.D. and CV) in hatching success across temperatures, with larger females producing offspring with maintained performance (less sensitive) across temperature treatments, indicative of flatter reaction norms and broader thermal niches. This suggests that maintaining the size distribution of fish populations, for instance through regulations of size-selective fisheries, may be important to aid the long-term productivity and viability of fish populations and ultimately conserve the function and services of ecosystems.